Improving Early Childhood Social-Emotional Intelligence through Role-Playing Methods In Group B - Arkam Lahiya; La Hasini; Tofhan Mamonto; Merdi F. Mamonto; Sabil Mokodenseho (Bulletin of Early Childhood, 2022)
Role-playing is a learning method easily applied in early childhood education. Children easily model the characters they like and become their favorites. With role-playing, all aspects of child development can quickly be developed. However, it needs direction and guidance from the teacher so that the desired outcome can develop properly. Therefore, this study discusses how role-playing can develop the social-emotional development aspects of early childhood in group B. This study uses classroom action research methodology. The research was conducted on 18 children in group B. The results of this study show the success of role-playing in developing the social-emotional aspects of early childhood. Through the learning cycle carried out, there are most children whose social-emotional development aspects develop as expected. Keywords: Social-Emotional Intelligence, Role Playing Methode, Early Childhood